Efficient Near-Infrared Luminescence of Self-Assembled Platinum(II) Complexes: From Fundamentals to Applications - Wei, Yu-Chen; Kuo, Kai-Hua; Chi, Yun; Chou, Pi-Tai (Accounts of chemical research, 2023)
Conspectus Designing bright and efficient near-infrared (NIR) emitters has drawn much attention due to numerous applications ranging from biological imaging, medical therapy, optical communication, and night-vision devices. However, polyatomic organic and organometallic molecules with energy gaps close to the deep red and NIR regime are subject to dominant nonradiative internal conversion (IC) processes, which drastically reduces the emission intensity and exciton diffusion length of organic materials and hence hampers the optoelectronic performances. To suppress nonradiative IC rates, we suggested two complementary approaches to solve the issues: exciton delocalization and molecular deuteration. First, exciton delocalization efficiently suppresses the molecular reorganization energy through partitioning to all aggregated molecules. According to the IC theory together with the effect of exciton delocalization, the simulated nonradiative rates with the energy gap ΔE = 104 cm–1 decrease by around 104 fold when the exciton delocalization length equals 5 (promoting vibronic frequency ω l = 1500 cm–1). Second, molecular deuterations reduce Franck–Condon vibrational overlaps and vibrational frequencies of promoting modes, which decreases IC rates by 1 order of magnitude in comparison to the rates of nondeuterated molecules under ΔE of 104 cm–1. Although deuteration of molecules has long been attempted to increase emission intensity, the results have been mixed. Here, we provide a robust derivation of the IC theory to demonstrate its validity, especially to emission in the NIR region. The concepts are experimentally verified by the strategic design and synthesis of a class of square-planar Pt(II) complexes, which form crystalline aggregates in vapor deposited thin films. The packing geometries are well characterized by the grazing angle X-ray diffraction (GIXD), showing domino-like packing arrangements with the short ππ separation of 3.4–3.7 Å. Upon photoexcitation, such closely packed assemblies exhibit intense NIR emission maximized in the 740–970 nm region through metal–metal-to-ligand charge transfer (MMLCT) transition with unprecedented photoluminescent quantum yield (PLQY) of 8–82%. To validate the existence of exciton delocalization, we applied time-resolved step-scan Fourier transform UV–vis spectroscopy to probe the exciton delocalization length of Pt(II) aggregates, which is 5–9 molecules (2.1–4.5 nm) assuming that excitons mainly delocalized along the direction of ππ stacking. According to the dependence of delocalization length vs simulated IC rates, we verify that the observed delocalization lengths contribute to the high NIR PLQY of the aggregated Pt(II) complexes. To probe the isotope effect, both partially and completely deuterated Pt(II) complexes were synthesized. For the case of the 970 nm Pt(II) emitter, the vapor deposited films of per-deuterated Pt(II) complexes exhibit the same emission peak as that of the nondeuterated one, whereas PLQY increases ∼50%. To put the fundamental studies into practice, organic light-emitting diodes (OLEDs) were fabricated with a variety of NIR Pt(II) complexes as the emitting layer, showing the outstanding external quantum efficiencies (EQEs) of 2–25% and the remarkable radiances 10–40 W sr–1 m–2 at 740–1002 nm. The prominent device performances not only successfully prove our designed concept but also reach a new milestone for highly efficient NIR OLED devices. This Account thus summarizes our approaches about how to boost the efficiency of the NIR emission of organic molecules from an in-depth fundamental basis, i.e., molecular design, photophysical characterization, and device fabrication. The concept of the exciton delocalization and molecular deuteration may also be applicable to a single molecular system to achieve efficient NIR radiance, which is worth further investigation in the future.